2003
DOI: 10.1016/s0014-5793(03)01460-1
|View full text |Cite
|
Sign up to set email alerts
|

In vivo formation of glutamyl‐tRNAGln in Escherichia coli by heterologous glutamyl‐tRNA synthetases

Abstract: Two types of glutamyl-tRNA synthetase exist: the discriminating enzyme (D-GluRS) forms only Glu-tRNA Glu , while the non-discriminating one (ND-GluRS) also synthesizes Glu-tRNA Gln , a required intermediate in protein synthesis in many organisms (but not in Escherichia coli). Testing the capacity to complement a thermosensitive E. coli gltX mutant and to suppress an E. coli trpA49 missense mutant we examined the properties of heterologous gltX genes. We demonstrate that while Acidithiobacillus ferrooxidans Glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 23 publications
2
14
0
Order By: Relevance
“…33,54 These translation errors could be not only tolerated, but also might be beneficial under certain stressful environmental conditions similar to what have been observed for other examples of errors in translation. Amino acid "mis-incorporation" has been proposed to protect cells from oxidative stress through the incorporation of extra methionines in proteins or from the immune system by enhancing the antigen variability.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…33,54 These translation errors could be not only tolerated, but also might be beneficial under certain stressful environmental conditions similar to what have been observed for other examples of errors in translation. Amino acid "mis-incorporation" has been proposed to protect cells from oxidative stress through the incorporation of extra methionines in proteins or from the immune system by enhancing the antigen variability.…”
Section: Discussionsupporting
confidence: 69%
“…Most reported differences in tRNA recognition are due to changes at the enzyme level. Nevertheless, the fact that some ND-GluRSs charge only tRNA Glu or tRNA Gln from E. coli (that contains only discriminating enzymes) 32,33 suggests that some differences between tRNA Glu and tRNA Gln must be suppressed in order to allow GluRS to be non-discriminant.…”
Section: Recognition Of Trna By Nd-glursmentioning
confidence: 99%
See 1 more Smart Citation
“…More often, however, the unintended synthesis of noncognate aa-tRNAs presents a threat to the accuracy of translation. Consequently a variety of quality control strategies are employed by the cell to ensure that typically only about one in every 10 4 codons is mistranslated, even though significantly higher rates at particular codons can be tolerated (Ruusala et al 1982;Kurland 1992;Min et al 2003;Nú ñ ez et al 2004). Aside from codon-anticodon pairing (Ogle et al 2003), the mechanisms of translational quality control are broadly of three types; specificity of substrate selection by aa-tRNA synthetases, proofreading, and exclusion from the ribosome.…”
Section: Quality Control and Aa-trnamentioning
confidence: 99%
“…The next step in protein synthesis requires the association of aa-tRNAs with translation factors, and this is used to provide an additional checkpoint. Although EF-Tu discrimination is not absolute (Min et al 2003;Nú ñ ez et al 2004), it can distinguish both precursor noncognate tRNAs (see above) and other incorrectly charged tRNA species ; Asahara and Uhlenbeck 2002), whereas initiation factor 2 specifically binds initiator aa-tRNAs (Mayer et al 2003). Finally, it has been suggested that the ribosome itself might also provide some degree of selectivity towards cognate aa-tRNAs .…”
Section: Beyond Aa-trna Synthesismentioning
confidence: 99%